Sistema plantio direto orgânico: rotações de cultura e controle mecânico de plantas espontâneas no sudoeste do Paraná - Reginatto, Maicon (2023)
The use of cover crops in crop rotation associated with mechanical control are the main alternatives for the control of weeds in organic no-tillage system. The use of these practices in organic production has become a fundamental element in working with an agriculture that seeks to reduce the impact of this activity on the environment. The rotation of crops with cover crops helps to improve the physical, chemical and biological characteristics of the soil, increasing the levels of straw, enabling the cultural control of weeds. The mechanical control of weeds without turning over the soil helps to maintain the straw on the ground, reducing the infestation of weeds and enhancing the increase in crop productivity. The present work was developed at UNEPE – Organic of the UTFPR, Dois Vizinhos city. Two case studies were carried out. Case study 1 took place between July 2018 and July 2021 and aimed to evaluate the performance of 16 crop rotations, including commercial crops and cover crops in an organic no-tillage system. In case study 2, carried out between August 2019 and May 2023, it sought to validate a mechanical control system for spontaneous plants, based on a public-private partnership with Company Gebana Brasil by Technical Cooperation Agreement between the company and UTFPR through CNPq in the DAI/CNPq program. In case study 1, treatment 2 (black oats/ soybean/ c. juncea/ black oats/ soybean/ lablab/ consortium/ corn/ c.juncea/ black oats) appears to be an excellent strategy by combining the biological productivity of the system ( kg of straw) which over time will result in improved soil attributes by adding straw to the system. While treatment 14 (black oats/ beans/ c. juncea/ consortium/ beans/ mix/ black oats/ soybean/ c. juncea/ consortium) is presented as one of the best alternatives among the 16 tested by associating greater biological productivity of straw with greater economic return. Organic soy has a higher net return than cultivation of transgenic soy, due to the 30% bonus on the value of transgenic soy, which means that the partial net profit is close to 30 bags of soy per ha/year. Based on the experiments carried out, it was possible to verify that the control system for spontaneous plants based on rolls has the potential to control plants in the initial stage.